Membrane transport systems and the biodegradation potential and pathogenicity of genus Rhodococcus - De Carvalho, Carla C.; Costa, Sofia S.; Fernandes, Pedro; Couto, Isabel; Viveiros, Miguel (Frontiers in Physiology, 2014)
The Rhodococcus genus contains species with remarkable ability to tolerate toxic compounds and to degrade a myriad of substrates. These substrates have to cross a distinctive cell envelope dominated by mycolic acids anchored in a scaffold of arabinogalactan covalently attached to the cell wall peptidoglycan, and a cellular membrane with phospholipids, whose composition in fatty acids can be rapidly altered in response to environmental conditions. The hydrophobic nature of the cell envelope facilitates the entrance of hydrophobic molecules but some substrates require active transport systems. Additionally, toxic compounds may also be extruded by energy spending efflux systems. In this review, physiological evidences of the use of transport systems by Rhodococcus strains and genomic studies that corroborate their existence are presented and discussed. The recently released complete genomes of several Rhodococcus strains will be the basis for an in silico correlation analysis between the efflux pumps present in the genome and their role on active transport of substrates. These transport systems will be placed on an integrative perspective of the impact of this important genus on biotechnology and health, ranging from bioremediation to antibiotic and biocide resistance.